National health insurance membership in Indonesia: Do socio-economic elements matter? - Misnaniarti; Wahyu Pudji Nugraheni; Agung Dwi Laksono; Asep Kusnali; Irfan Ardani; Leny Latifah; Rofingatul Mubasyiroh; Diah Yunitawati; Tati Suryati Warouw (PLoS ONE, 2025)
The Indonesian government released a National Health Insurance (NHI) policy to realize universal health coverage (UHC) in Indonesia, yet disparities in membership persist. The study examined the influence of various socio-economic factors, including education, employment, and wealth status, on National Health Insurance (NHI) membership in Indonesia. Using a cross-sectional design, this study examined 1,223,377 individuals. The level of education was utilized as the exposure variable, while NHI membership served as the outcome variable. The analysis included residence, age, gender, marital status, and occupation as covariates. In the final stage, logistic multinomial regression was implemented. Based on the findings of this study, Indonesia’s coverage for NHI membership in 2023 was 72.5%. Higher education levels are associated with increased likelihood of NHI participation, supporting the notion that education promotes greater access to Universal Health Coverage (UHC). Wealth status and demographic factors such as age and marital status also significantly associated with NHI membership. According to the results, the study concluded that education level and wealth status significantly influence NHI membership in Indonesia. Demographic factors also play essential roles. Tailored interventions addressing these factors are necessary to improve NHI enrollment and achieve universal health coverage.